2019
DOI: 10.1158/1541-7786.mcr-18-0256
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Detection of Bruton's Tyrosine Kinase Inhibition in Mantle Cell Lymphoma Cells

Abstract: Current methods to evaluate effects of kinase inhibitors in cancer are suboptimal. Analysis of changes in cancer metabolism in response to the inhibitors creates an opportunity for better understanding of the interplay between cell signaling and metabolism and, from the translational perspective, potential early evaluation of response to the inhibitors as well as treatment optimization. We performed genomic, metabolomic, and fluxomic analyses to evaluate the mechanism of action of the Bruton's tyrosine kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In contrast, ibrutinib-resistant MCL cells display increased OxPhos, and combining ibrutinib to IACS-010759 blocks tumor growth [ 375 ]. Ibrutinib resistance also correlates to higher glutaminolysis, that renders glutaminase inhibitor CB-839 efficient at killing ibrutinib-resistant MCL cells [ 429 ].…”
Section: Targeting Metabolic Reprogramming In B Cell Malignancies—pre...mentioning
confidence: 99%
“…In contrast, ibrutinib-resistant MCL cells display increased OxPhos, and combining ibrutinib to IACS-010759 blocks tumor growth [ 375 ]. Ibrutinib resistance also correlates to higher glutaminolysis, that renders glutaminase inhibitor CB-839 efficient at killing ibrutinib-resistant MCL cells [ 429 ].…”
Section: Targeting Metabolic Reprogramming In B Cell Malignancies—pre...mentioning
confidence: 99%
“…The Bruton tyrosine kinase (BTK) inhibitor ibrutinib abolishes BCR signaling and has emerged as a potent therapeutic option for r/r MCL. BTK-blockade markedly affected the (ibrutinib-responsive) MCLs' metabolic activity including glycolysis and the TCA cycle (33). Interestingly, Zhang et al reported that ibrutinib-resistant MCLs depict a metatobolic rewiring toward glutaminolysis-fueled OxPhos (34).…”
Section: Mantle Cell Lymphoma (Mcl)mentioning
confidence: 99%
“…The most studied example of nutrient competition is the increased glucose consumption by malignant cells caused by elevated expression levels of glucose transporters and enzymes of the glycolytic machinery {as seen in BCR-DLBCL [e.g., GAPDH expression ( 52 ) and lactate secretion ( 13 )], transformed FL [e.g., GAPDH and aldolase A ( 27 , 28 )], MCL [e.g., glycolytic flux ( 33 )], and CLL in the LN-/BM-niche [e.g., glycolytic flux and key glycolytic enzymes ( 44 )]}. This is detrimental for T- and NK-cells as their proliferation, activation, and differentiation is highly dependent on glucose as a fuel for both aerobic glycolysis and OxPhos [reviewed in ( 53 )].…”
Section: Lymphoma Metabolism and Its Potential Impact On Anti-lymphommentioning
confidence: 99%
“…Recent investigations demonstrated that the genes involved in OXPHOS (e.g., ETC complexes I, III, IV, V) were largely dependent on MYC for translation (Singh et al 2019). Another line of evidence supports a role for glutamine-dependent OXPHOS as a mediator of ibrutinib resistance in mantle cell lymphoma (MCL), potentially driven by MYC and TOR activity (Lee et al 2019;Zhang et al 2019a). Ibrutinib-resistant MCL was uniquely dependent on glutamine uptake and glutaminolysis; disruption of glutamine metabolism or ETC complex I increased ROS, induced energetic stress, and overcame resistance to ibrutinib.…”
Section: Oxidative Phosphorylationmentioning
confidence: 99%